PERANCANGAN APLIKASI ANTARMUKA SISTEM PEMANTAUAN KESEHATAN AYAM TERNAK BERDASARKAN PERILAKU MAKAN AYAM DALAM KANDANG DENGAN COMPUTER VISION DAN IOT - Nizzah Khusnunnisa; Adharul Muttaqin; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2022)
The Center for Domestic Trade Studies of the Ministry of Trade of the Republic of Indonesia stated that chicken meat is one of the main commodities in meeting the animal protein needs of the community. This causes the community's need for broiler meat to be quite high. The high number of people's need for broilers makes the health of broilers something that deserves attention. The environmental condition of the chicken coop is one of the factors that affect the health of chickens. To maintain the health of chickens, it is very important to create a comfortable atmosphere for chickens, by paying attention to air circulation and humidity, and adjusting the density of the cage. For now, monitoring temperature and humidity, as well as setting the density of the cage is still carried out manually will take a lot of time and require a lot of manpower. For this reason, we need an application that can help monitor the temperature, humidity, and density of the cage. In this study, an application design assisted by the PyQt5 library will be carried out and aims to monitor the temperature, humidity, behavior, and distribution of chickens through an application that will be developed with the help of Internet of Things technology and Computer Vision technology. Keywords: Broiler chicken, computer vision, YOLOv4, PyQt5, Io